Aktualisasi Teologi Sosial Melalui Tradisi Ta’ziah di Malam Ke-3 Ke-40 Ke-100 Hari (Analisis Perbandingan Muhammadiyah dengan Al-Wasliyah) Kel. Tegal Sari I Kec. Medan Area - Khoirul Najri; Musaddad Lubis; Sholahuddin Ashani (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
Social theology at the ta'ziah event in Tegal Sari 1 Village, Medan Area sub-district which is a conversation in the community with the existence of the Muhammadiyah and Al-Wasliyah groups, each of whom has an opinion about ta'ziah at the tahlilan event, therefore we associate it with socializing to the surrounding community and is a social wisdom as well as worship in our lives, with that we can help our brothers, relatives and our closest neighbors. This study aims to find out how wisdom is in socializing by making the ta'ziah tradition at the tahlilan event on the 3rd 40th night of the 100th day with a comparative analysis of Muhammadiyah and Al-Wasliyah in Tegal Sari 1 Village, Medan Area District. this type of research is a field research (field research) with a qualitative approach that produces descriptive data in the form of writing and behavior that can be observed from the subject, data collection techniques by means of interviews, observation and documentation. The results showed that the wisdom of carrying out the ta'ziah tradition at the tahlilan event at the place of the calamity expert and is a wisdom in worship, as for those that provide several factors: first, namely social factors: which strengthen the relationship with relatives, neighbors, and relatives by providing help and advice good for his brother who is a socialist towards fellow humans because they gather at the place of disaster experts. Second, the factor of wisdom in carrying it out: namely increasing the quality of worship by reciting verses of the Qur'an and giving us benefits which we can be fluent in reading. Religion is a guide for human life in human life in overcoming the problems faced so that it can reconcile the human body and mind. Religion as a human benchmark in shaping personality and behavior that serves to understand and understand each other between religious communities in each individual or group.